2018
DOI: 10.1021/acs.jnatprod.7b00564
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Flavonoids and Flavonoid Glycosides from Myrsine africana and Their Inhibitory Activities against Mushroom Tyrosinase

Abstract: Bioassay-guided fractionation of the methanol extract of the shoots of Myrsine africana led to the isolation of the new compound myricetin 3-O-(2″,4″-di-O-acetyl)-α-l-rhamnopyranoside (9) and 11 known compounds. The known compounds quercetin 3-O-(3″,4″-di-O-acetyl)-α-l-rhamnopyranoside (8), rutin (10), quercetin 3-O-α-l-rhamnopyranoside (11), and myricetin 3-O-α-l-rhamnopyranoside (12) are reported for the first time from the methanol extract of the shoots of M. africana. Compounds 10 and 12 showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
(59 reference statements)
1
26
0
4
Order By: Relevance
“…Low IC50 values against both monophenolase and diphenolase activty of mushroom tyrosinase have been very recently reported for p-coumaric and caffeic acid [66], belonging to the cinammic acid family ( Figure 7). The IC50 values together with structural formulas for other phenolic compounds widely distributed in nature that have been the subject of studies that appeared in the last five years [53,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Low IC 50 values against both monophenolase and diphenolase activty of mushroom tyrosinase have been very recently reported for p-coumaric and caffeic acid [66], belonging to the cinammic acid family ( Figure 7). Moving to simple phenols, significant inhibition activity has been described for 4-hydroxybenzyl alcohol (IC50 = 6 μM) [61] and isoeugenol (IC50 = 33.3 μM) [62], which would appear more efficient than resorcinol [55] or rhododendrol [63] themselves.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
See 1 more Smart Citation
“…Low IC50 values against both monophenolase and diphenolase activty of mushroom tyrosinase have been very recently reported for p-coumaric and caffeic acid [66], belonging to the cinammic acid family ( Figure 7). The IC50 values together with structural formulas for other phenolic compounds widely distributed in nature that have been the subject of studies that appeared in the last five years [53,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Low IC 50 values against both monophenolase and diphenolase activty of mushroom tyrosinase have been very recently reported for p-coumaric and caffeic acid [66], belonging to the cinammic acid family ( Figure 7). Moving to simple phenols, significant inhibition activity has been described for 4-hydroxybenzyl alcohol (IC50 = 6 μM) [61] and isoeugenol (IC50 = 33.3 μM) [62], which would appear more efficient than resorcinol [55] or rhododendrol [63] themselves.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Low IC50 values against both monophenolase and diphenolase activty of mushroom tyrosinase have been very recently reported for p-coumaric and caffeic acid [66], belonging to the cinammic acid family (Figure 7). The IC50 values together with structural formulas for other phenolic compounds widely distributed in nature that have been the subject of studies that appeared in the last five years [53,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] The IC 50 values together with structural formulas for other phenolic compounds widely distributed in nature that have been the subject of studies that appeared in the last five years [53,62,63,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] are also reported in Figures 4-8.…”
Section: Natural Phenolic Inhibitors Of Mushroom Tyrosinasementioning
confidence: 99%
“…Previous studies have identified and characterised myrsinoside B (94.39% purity) amongst other compounds (Kishore et al, 2018). Lall et al (2017) reported noteworthy elastase inhibition for M. africana (28.04 µg/ml) and myrsinoside B (4.69 µg/ml).…”
Section: Introductionmentioning
confidence: 96%
“…It is also used in various culinary applications as a fragrance, flavoring agent, spice, and appetizer (Ahmad et al, 2011b).Additional uses include as an anthelmintic, antibacterial, for the treatment of boils, and scanty urine (Watt and Breyer-Brandwijk, 1962;Killick, 1969;Githiori et al, 2002;Abbasi et al, 2010). The reported use of M. africana as a blood purifier spurs interest around its potential application as an anti-wrinkle agent as such agents often play an important role in maintaining healthy skin (Kishore et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation